(untitled) (Journal of Applied Learning and Teaching, 2024)
The proliferation of artificial intelligence (AI) and robots is precipitating profound shifts in several sectors, including education. A pressing inquiry arises among scholarly communities: To what extent will the advancement of technology supplant or surpass the conventional responsibilities of educators? The process of dissecting and analysing this subject is intricate, with many layers to consider. Demonstrating this phenomenon, a British educational institution has recently designated an artificial intelligence (AI) robot named Abigail Bailey as one of its “co-headteachers.” Abigail possesses sophisticated machine learning skills that enable her to process extensive information efficiently, akin to AI systems such as ChatGPT that simplify user interactions through algorithmic-generated answers. This breakthrough raises the question: Does this mark the beginning of a period in which robots assume a prominent position in education, hence threatening the traditional duties of educators? This opinion piece explores the essential factors that need to be taken into account.